2019
DOI: 10.1080/09593969.2019.1687103
|View full text |Cite
|
Sign up to set email alerts
|

Motives and barriers affecting consumers’ co-creation in the physical store

Abstract: The rise of e-commerce has caused a dramatic shift in consumer behaviour, putting pressure on physical stores to offer a more personalised and service-oriented offering. This paper investigates one strategy retailers might apply in this context: in-store consumer cocreation. Research has predominantly focused on online-based consumer co-creation in new product and service development. We argue that with increased focus on digitalisation and consumer experiences in physical retail, this type of co-creation will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…We argue that similar argumentation is also valid in case of knowledge sharing between consumer and provider because developmental motives can be a significant motivational factor for patients to share knowledge and co-create value. Moreover, concerted motives have been found to positively influence knowledge sharing leading to value co-creation by consumers in a physical store setting in a recent study by Schüler et al (2019). Hence, both developmental and concerted motives have the potential to support knowledge sharing value co-creation between consumers and health-care service providers.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 1 more Smart Citation
“…We argue that similar argumentation is also valid in case of knowledge sharing between consumer and provider because developmental motives can be a significant motivational factor for patients to share knowledge and co-create value. Moreover, concerted motives have been found to positively influence knowledge sharing leading to value co-creation by consumers in a physical store setting in a recent study by Schüler et al (2019). Hence, both developmental and concerted motives have the potential to support knowledge sharing value co-creation between consumers and health-care service providers.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…In an increasingly competitive landscape, organizations are struggling to engage with their consumers and motivate them to participate in value co-creation activities by sharing knowledge with them (Archer-Brown and Kietzmann, 2018; O’Hern and Rindfleisch, 2010). It has further been argued that managers need specific guidance on how to develop and implement a value co-creation strategy that will move beyond the metaphorical view of value co-creation used in many studies (Grönroos and Gummerus, 2014; Schüler et al , 2019). At the same time, the role of (service) context for better understanding of value co-creation has been highlighted in recent studies (Caputo et al , 2019; Etgar, 2008; Neghina et al , 2017; Vargo and Lusch, 2004, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of memorable and satisfactory visitor with disabilities experiences, barriers are defined as all obstacles, whether physical [48] sensory [49], cultural, or social [21,50], that limit or impede people's ability to use products, services, and environments [51].…”
Section: Barriers To the Memorable Inclusive Experiencementioning
confidence: 99%
“…Therefore, creating conditions for engaging purchasers in creating a marketing offer is extremely important in their case. This applies to all offerors of products of this kind, including restaurateurs (Bowden, 2009), retailers (Sch€ uler et al, 2020), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Admittedly, attempts have been made to look for dimensions of purchasers' engagement, including the following three dimensions (Vivek et al, 2014): conscious attention, enthused participation and social connection; however, involvement is not synonymous with prosumer activity and, moreover, these dimensions have not included lifestyle. The focus has been placed on completely different aspects of prosumer cooperation such as its genesis (Charitsis, 2016;Tian et al, 2017), scope and / or environment (Hollebeek et al, 2014;Barger et al, 2016;Baruk, Co-creation of a food marketing offer 2019; Khrystoforova and Siemieniako, 2019), positive effects (Kennedy and Guzm an, 2016), negative consequences (Charitsis et al, 2019), causes (Sch€ uler et al, 2020;Cova and Cova, 2012;Bagozzi and Dholakia, 2006), etc. On this basis, it can be concluded that there are cognitive and research gaps related to considerations on the readiness to co-create various elements of the marketing offer, especially in the case of a food marketing offer, in the context of a lifestyle represented by a given person resulting from their personality type.…”
Section: Literature Reviewmentioning
confidence: 99%